Cortical visual impairment : an approach to assessment and intervention - Roman-Lantzy, Christine, 1951- (AFB Press, American Foundation for the Blind, 2018)
Cortical Visual Impairment: An Approach to Assessment and Intervention provides educators, therapists, physicians, and parents of children with CVI with an understanding of the condition and a complete framework for assessment and intervention. The new and revised content in this second edition brings the book up-to-date with new research and insights into CVI, its development and progression, and the best approaches to assessment and intervention with children affected by this condition. As in the previous edition, assessment forms, including the CVI Range and CVI Progress Chart, provide a comprehensive method for evaluating the functional vision status of, and program planning for, children with CVI.